Lipoteichoic Acid and Lipopolysaccharide can Activate Antimicrobial Peptide Expression in the Tobacco Hornworm Manduca sexta - Rao, Xiang-Jun (2010)
Activation of prophenoloxidase and synthesis of antimicrobial peptides (AMPs) are two important innate immune mechanisms in insects. In the current study, we investigated immune responses activated by three major bacterial components, lipopolysaccharide (LPS) (including rough mutants of LPS), lipoteichoic acid (LTA), and peptidoglycan (PG), in the larvae of a lepidopteran insect, Manduca sexta. We found that two DAP (Diaminopimelic acid)-type PGs from Escherichia coli and Bacillus subtilis were much more potent than LPS and LTA from the respective bacteria as well as a Lysine-type PG in activation of prophenoloxidase in M. sexta larval plasma in vitro. Transcription levels of AMP genes, such as Attacin, Lebocin and Moricin genes, in the hemocytes and fat body of larvae were significantly induced by smooth LPS (TLR4grade) and rough mutants of LPS (TLRgrade(™)), synthetic lipid A, LTA, and PG. LPS from E. coli and LTA from B. subtilis activated AMP expression to significantly higher levels than PGs from the respective bacterial strains, and smooth LPS were more potent than lipid A and rough mutants of LPS in activation of AMP expression. Our results demonstrated for the first time that LTA can activate AMP expression, and different moieties of LPS may synergistically activate AMP expression in M. sexta.